Biallelic loss of function variants in STAG3 result in primary ovarian insufficiency. Issue 5 (November 2021) - Demain, Leigh A.M.; Boetje, Eline; Edgerley, Jonathan J.; Miles, Emma; Fitzgerald, Cheryl T.; Busby, Gail; Beaman, Glenda M.; O'Sullivan, James; O'Keefe, Raymond T.; Newman, William G.
Abstract: Research question: Does a genetic condition underlie the diagnosis of primary ovarian insufficiency (POI) in a 21-year-old woman with primary amenorrhoea? Design: A karyotype and genetic testing for Fragile X syndrome was undertaken. A next-generation sequencing panel of 24 genes associated with syndromal and non-syndromal POI was conducted. Results: A nonsense variant c.1336G>T, p.(Glu446Ter) and whole gene deletion in STAG3 were identified. Conclusions: Biallelic loss of function variants in STAG3 are associated with primary ovarian failure type 8 and are a rare cause of POI.